Energy Evaluation for Lignite Pyrolysis by Solid Heat Carrier Coupled with Gasification - Yi, Qun; Feng, J.; Lu, B.; Deng, J.; Yu, C.; Li, W. (American Chemical Society, 2013)
In order to utilize lignite in a clean and highly efficient way, an energy system for lignite pyrolysis by solid heat carrier coupled gasification is proposed in this study. The process is simulated and analyzed by Aspen Plus 11.1 on the basis of experimental data. The energy consumption distribution of the system and the mass ratio of the solid heat carrier to lignite, the most important technological parameters, are revealed. The choice of gasifier has the greatest impact on the energy efficiency of the system. Results show that, with a lignite handling capacity of 41.7 t•h-1, the yields of tar and coal gasified gas are 1.6 and 25.7 t•h-1, respectively, and 17% of the char is burnt to supply energy for the system while the remainder is used in the gasifier. Also, the surface moisture present in lignite and the phenol water from the tar can be utilized as the gasification agent in the coupled process, saving up to 8.9 t•h-1 water and decreasing the handling capacity of phenol water by 2.7 t•h-1, thereby reducing the net volume of polluted water emitted by the system. It is possible for the system as a whole to achieve an energy efficiency of up to 85.8%. The study also shows that the majority of the energy used by the system is consumed during the drying and pyrolysis processes. Exploiting new technology, integrating and optimizing the energy use of the system to reduce energy consumption will be beneficial to improving the overall system performance.